Land Based Conflicts Influencing Land Ownership by Religious Groups in Vihiga County, Kenya - Nyonje Owlenyi, Billy E.; Shitote, Zacharia (African Journal of Education,Science and Technology (AJEST), 2025)
Vihiga forms part of the counties with the dense population in Kenya having its recent population density of one thousand and forty-five people per square km. This population has exerted massive pressure on existing land resource leading to fragmentation of land together with battles over land resource. The religious groups in Vihiga County have not been exempted from these land conflicts. Nevertheless, the weightiness of the problem has not been steadily evaluated and documented. This research investigated conflicts facing land ownership by religious groups in Vihiga County and proposed policy and planning interventions. A descriptive survey research design was employed for the research where the target population was 350 consisting 150 pastors and 200 church members. The sample size was 215 respondents that included 15 pastors and 200 church members chosen using purposive sampling and simple random sampling. Secondary data was collected through literature search while primary data were gathered with the use of questionnaires, check lists, observation, key informant interviews, focus group discussions and interview guide. The data was then analyzed using descriptive statistics in the Statistical Package Social Science (SPSS) Version 20 after which they were presented in charts, tables, text and photographs. Results disclosed a strong negative association between level of education and prevalence of land-related conflicts among congregants in churches within Vihiga County. It is recommended that religious groups in Vihiga County should have their land documented to enhance land ownership. Policy and planning interventions for increasing access to education by residents of Vihiga County should be enhanced by the government, so as to reduce cases of violence and conflicts related to land ownership.